The effect of alfacalcidiol and metformin on phenotype manifestations in women with polycystic ovary syndrome - a preliminary study - Dravecká, Ingrid; Figurová, Jana; Javorský, Martin; Petríková, Jana; Vaľková, Martina; Lazúrová, Ivica (Physiological research, 2016)
Aim of this study was to evaluate the effect of vitamin D supplementation in obese, insulin resistant and vitamin D deficient PCOS women on biochemical and clinical hyperandrogenism and menstrual irregularity in comparison to effect of metformin or combined metformin plus vitamin D therapy. Thirty nine PCOS women were randomized into three groups and treated with alfacalcidiol (Group 1), combined alfacalcidiol and metformin therapy (Group 2) and metformin (Group 3) for 6 months. Serum TST, fTST, DHEAS, LH and LH/FSH were measured before and after six months of treatment. Menstrual cycle regularity, hirsutism, acne and pregnancy rate were assessed at the same time. There was a significant decrease in TST levels in the Group 2 and slight but not significant decrease in the Group 3. No significant changes in other parameters (fTST, DHEAS, LH, LH/FSH) have been found after 6 months therapy in all three groups. An improvement of menstrual cycle was detected in 78 % of patients in Group 1 (p<0.04), 80 % in the Group 2 (p<0.03) and in 90 % in the Group 3 (p<0.002), respectively. There was no significant improvement of acne and hirsutism in all three groups (all p not significant). Pregnancy rate was higher in the Group 3 as compared with Groups 1 and 2 (67 % vs. 0 % and 25 %, respectively), however without statistical significance. Vitamin D administration has no significant effect on androgen levels and clinical features of hyperandrogenism in obese vitamin D deficient PCOS women. However, it can potentiate effect of metformin on testosterone levels and LH/FSH ratio but not on clinical hyperandrogenism and pregnancy rate.
Keywords: syndrom polycystických ovarií; obezita; Pregnancy; Humans; metformin; Insulin Resistance; Polycystic Ovary Syndrome; Pregnancy Rate; Female; mladý dospělý; dospělí; Metformin; Hydroxycholecalciferols; Phenotype; lidé; hyperandrogenismus; pilotní projekty; Pilot Projects; menstruační cyklus; Hypoglycemic Agents; Adult; hydroxycholekalciferoly; ženské pohlaví; Menstrual Cycle; inzulinová rezistence; fenotyp; těhotenství; Hyperandrogenism; Young Adult; hypoglykemika; Obesity; úhrn těhotenství na počet žen v reprodukčním věku